Study of role of vitamin C in type 2 diabetes mellitus patients - Eda, Shashikala; Motgi, Somnath; Singh, Rohith; B. N., Vijay Raghawa Rao (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Diabetes mellitus (DM) is the most common non-communicable diseases in the present millennium which has become a global public health problem. The treatment of type 2 Diabetes mellitus (T2 DM) often is initiated with monotherapy of oral antidiabetic drugs (OADs), which often do not decrease the plasma sugar levels effectively and consistently that will reduce short term and long-term complications associated with T2 DM. Hence the current study is aimed to determine the effectiveness of vitamin C supplementation with standard OADs on glycemic control. Methods: This study consisted of 120 T2 DM patients with 80 males and 40 females with a mean age of 50.88 yrs were divided into four groups with equal number of males and females in each group depending upon the OADs they received in solo or with vitamin C for 12 weeks. After the written consent, a detail clinical history, clinical examination, biochemical investigations including fasting plasma sugar (FPS), post prandial plasma sugar (PPS), glycosylated hemoglobin (HBA1c), serum creatinine, serum electrolytes, chest X-ray PA view and standard ECG were done. Repeat FPS, PPS and HBA1c were done after 4, 8 and 12 weeks of study. Results: After 12 weeks of study FBS, PPS and HBA1c decreased significantly (p<0.01) in study groups (Metformin and teneligliptin with vitamin C) as compared to control groups (OADs without vitamin C). Vitamin C supplementation with OADs found to be effective, well tolerated and devoid of any side effects. Conclusions: OADs are effective and affordable hypoglycemic agents with vitamin C supplementation.